A safe and effective atovaquone-proguanil therapeutic protocol for the treatment of avian Malaria by Plasmodium relictum in snowy owl (Bubo scandiacus) - Nicola Pugliese; Rossella Samarelli; Roberto Lombardi; Antonella Schiavone; Giuseppe Crescenzo; Elena Circella; Claudia Zizzadoro; Olimpia Lai; Medhat S. Saleh; Michela Prioletti; Antonio Camarda (Animals, 2023)
Avian malaria is a re-emerging threat to avian species worldwide. It is sustained by several protozoan species belonging to the genus Plasmodium, mainly Plasmodium relictum. The even wider diffusion of the disease, probably because of the increase in the areas covered by their mosquito vectors, may pose new risks for avian species lacking natural resistance (especially those from artic or sub-artic environments) or those hosted in structures like zoos and wildlife rescue centers. With that premise, this study describes the efficacy and safety of a therapeutic protocol to treat avian malaria in three snowy owls (Bubo scandiacus) hosted in a wildlife rescue center in Apulia, south of Italy, and affected by avian malaria by P. relictum. The protocol consisted of administering 10/4 mg/kg atovaquone/proguanil per os once a day for three consecutive days, repeating this seven days later. Seven days after the end of the treatment, P. relictum was not detected in the birds' blood and no adverse effects were observed during the 60 days of monitoring after the end of the treatment. Therefore, a therapeutic regimen of 10/4 mg/kg/day may be considered safe and effective in a valuable and endangered species such as B. scandiacus.